2019
DOI: 10.4103/apjon.apjon_76_18
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence as A Predictor of Health-Related Quality of Life in Breast Cancer Survivors

Abstract: Objective: The objective of this study is to explore the predictive role of emotional intelligence (EI) and its elements for health-related quality of life (HRQoL) dimensions in a sample of breast cancer survivors. Methods: This cross-sectional study was conducted in a single oncology clinic at a university hospital. A sample of breast cancer survivors ( n = 180) completed three questionnaires: Short-Form Health Survey SF-36 (the RAND 36-item)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…As stated above, in the oncological field, it has been demonstrated that the difficulty of regulating emotions is associated with greater emotional distress and depression. Likewise, adequate levels of emotional repair act as a protective element in adverse contexts, being related to greater adaptation to the disease [27,28]. In addition, it has been found that older women tend to pay less attention to their emotions [29], which can stimulate the appearance of negative emotional states and depressive symptoms [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…As stated above, in the oncological field, it has been demonstrated that the difficulty of regulating emotions is associated with greater emotional distress and depression. Likewise, adequate levels of emotional repair act as a protective element in adverse contexts, being related to greater adaptation to the disease [27,28]. In addition, it has been found that older women tend to pay less attention to their emotions [29], which can stimulate the appearance of negative emotional states and depressive symptoms [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, motives and outcomes related to psychological well-being do not change before and after intervention. This evidence shows that breast cancer survivors are strongly self-aware about their psychological needs, which may be useful in order to improve tailored and appropriate interventions [ 41 ]. Finally, taking time for themselves could be related to the need to take care of oneself, which is important for psychological well-being after a cancer experience in a first-centered and holistic view [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is described as having the ability to process emotional information, such as recognizing, creating, and controlling emotions, data on how to express emotions in oneself and others, and information on how to manage emotions for emotional development. Finding strategies to manage and adapt to one's own and other people's feelings is a crucial component of emotional intelligence 8 . Features of emotional intelligence play a critical role in overcoming stressful situations and carrying out good interpersonal interactions with family patients.…”
Section: Introductionmentioning
confidence: 99%
“…Wong and Law's emotional intelligence questionnaire (2002) consists of 16 items and includes four dimensions: evaluation and expression (1-4); emotional understanding and analysis(5)(6)(7)(8); use of emotions to facilitate thought(9)(10)(11)(12); and emotional regulation(13- 16). A 5-point Likert scale was assigned scores (1 = completely opposed, 5 = completely agree).…”
mentioning
confidence: 99%